Application of graph theory and webster method in traffic light settings at the tulip intersection in kefamenanu city - Sikas, Oktovianus R.; Mada, Grandianus Seda; Blegur, Fried Markus Allung; Nabu, Andreas Giovani (Universitas Islam Negeri Raden Intan Lampung, 2023)
The traffic light settings at several road intersections in Timor Tengah Utara Regency have not been regulated, taking into account the width of the road and the volume of vehicles. One of the intersections in question is the Eltari–Sonbay–L. Lake intersection road (Tulip intersection). At this intersection, traffic jams often occur because traffic light settings are not optimal, so it is necessary to have traffic regulations that pay attention to road width and vehicle volume. This research aims to find out how to regulate the duration of traffic lights using graph theory and the Webster method. This research is applied research. The data used is primary data, which includes road geometry and traffic volume data. The results of calculations using a compatible graph and the Webster method obtained two-time phases. Phase 1 for the Eltari road section (north and south) has a green light duration of 22 seconds, yellow 3 seconds, and red 27 seconds. Meanwhile, Phase 2 for Sonbay Road and L. Lake Road has a green, yellow, and red-light duration of 23 seconds, 3 seconds, and 26 seconds, respectively. These results look more optimal compared to the current ones, which only consist of one-time phase.